Development of a four‐axis moving phantom for patient‐specific QA of surrogate signal‐based tracking IMRT. Issue 12 (7th November 2016) - Mukumoto, Nobutaka; Nakamura, Mitsuhiro; Yamada, Masahiro; Takahashi, Kunio; Akimoto, Mami; Miyabe, Yuki; Yokota, Kenji; Kaneko, Shuji; Nakamura, Akira; Itasaka, Satoshi; Matsuo, Yukinori; Mizowaki, Takashi; et al.
Abstract : Purpose: The purposes of this study were two‐fold: first, to develop a four‐axis moving phantom for patient‐specific quality assurance (QA) in surrogate signal‐based dynamic tumor‐tracking intensity‐modulated radiotherapy (DTT‐IMRT), and second, to evaluate the accuracy of the moving phantom and perform patient‐specific dosimetric QA of the surrogate signal‐based DTT‐IMRT. Methods: The four‐axis moving phantom comprised three orthogonal linear actuators for target motion and a fourth one for surrogate motion. The positional accuracy was verified using four laser displacement gauges under static conditions (±40 mm displacements along each axis) and moving conditions [eight regular sinusoidal and fourth‐power‐of‐sinusoidal patterns with peak‐to‐peak motion ranges ( H ) of 10–80 mm and a breathing period ( T ) of 4 s, and three irregular respiratory patterns with H of 1.4–2.5 mm in the left–right, 7.7–11.6 mm in the superior‐inferior, and 3.1–4.2 mm in the anterior–posterior directions for the target motion, and 4.8–14.5 mm in the anterior–posterior direction for the surrogate motion, and T of 3.9–4.9 s]. Furthermore, perpendicularity, defined as the vector angle between any two axes, was measured using an optical measurement system. The reproducibility of the uncertainties in DTT‐IMRT was then evaluated. Respiratory motions from 20 patients acquired in advance were reproduced and compared three‐dimensionally with the originals. Furthermore, patient‐specific dosimetric QAs of DTT‐IMRT were performed for ten pancreatic cancer patients. The doses delivered to Gafchromic films under tracking and moving conditions were compared with those delivered under static conditions without dose normalization. Results: Positional errors of the moving phantom under static and moving conditions were within 0.05 mm. The perpendicularity of the moving phantom was within 0.2° of 90°. The differences in prediction errors between the original and reproduced respiratory motions were −0.1 ± 0.1 mm for the lateral direction, −0.1 ± 0.2 mm for the superior‐inferior direction, and −0.1 ± 0.1 mm for the anterior–posterior direction. The dosimetric accuracy showed significant improvements, of 92.9% ± 4.0% with tracking versus 69.8% ± 7.4% without tracking, in the passing rates of γ with the criterion of 3%/1 mm ( p < 0.001). Although the dosimetric accuracy of IMRT without tracking showed a significant negative correlation with the 3D motion range of the target ( r = − 0.59, p < 0.05), there was no significant correlation for DTT‐IMRT ( r = 0.03, p = 0.464). Conclusions: The developed four‐axis moving phantom had sufficient accuracy to reproduce patient respiratory motions, allowing patient‐specific QA of the surrogate signal‐based DTT‐IMRT under realistic conditions. Although IMRT without tracking decreased the dosimetric accuracy as the target motion increased, the DTT‐IMRT achieved high dosimetric accuracy.